Use of botulinum toxin for movement disorders - Carlos Henrique Ferreira Camargo; Hélio Afonso Ghizoni Teive (BioExcel Publishing Ltd, 2019)
The term movement disorders encompasses all disorders hypokinetic and hyperkinetic, which were previously known as extrapyramidal syndromes. With the definition of movement disorders and their diagnostic criteria and classifications, new studies for therapeutics could be performed. New drugs were launched, functional neurosurgery was developed, and the introduction of botulinum toxin (BoNT) for hyperkinesias was introduced. BoNT is an important therapy for dystonia, tics, myoclonus, and tremors. The aim of this review is to present the new and well-established uses of BoNT for movement disorders.